Yellow rice has its price - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Practically all irrigated rice in sub-Saharan Africa is prone to the rice yellow mottle virus (RYMV). Until the 1990s, the effects of RYMV were relatively modest but since then yield losses of up to 95% have occurred throughout the continent s rice...